(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Field experiments were conducted in the Grey Terrace Soil (Aeric Albaquept) under AEZ-28 at the Bangladesh Agricultural Research Institute (BARI) farm, Gazipur during summer seasons of 2010 and 2011 to determine the optimum rate of boron and molybdenum combination for maximizing the yield of summer country bean (var. BARI Sheem-3). Four levels each of B (0, 1, 2 and 3 kg ha-1 ) and Mo (0, 0.5, 1.0 and 1.5 kg ha-1 ) were used as treatment variables. The results indicated that application of B and Mo fertilizer combination exerted significant influence on the number of pods plant-1 , individual pod weight and pod yield ha-1 in both the years. The highest pod yield (9.58 t ha-1 in 2010 and 9.42 t ha-1 in 2011) was produced by the combination of 2 kg B and 1.5 kg Mo ha-1 and it was statistically identical with 2 kg B and 1.0 kg Mo ha-1 combination. Addition of B beyond 2 kg ha-1 along with higher doses of Mo created a detrimental effect to reduce yield irrespective of years. The results revealed that application of 2 kg B and 1 kg Mo ha-1 combination with a blanket dose of 50 kg N, 40 kg P, 60 kg K and 20 kg S ha-1 plus cowdung 5 t ha-1 might be optimum for summer country bean cultivation in Grey Terrace Soil of Gazipur. Bangladesh J. Agril. Res. 40(1): 71-76, March 2015